2018
DOI: 10.1080/22201181.2018.1510234
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography in mild, chronic liver disease: challenging conventional coagulation tests preceding liver biopsy

Abstract: Patients presenting for liver biopsy may have a deficiency of the synthetic function of the liver. They commonly undergo testing of their INR, which is used to decide if there may be a bleeding risk and if that needs to be mitigated by the administration of clotting factors. This study aimed to observe the coagulation profile of these patients via a thromboelastogram (TEG), and to search for a relationship between the traditionally used INR and the R-time of the TEG. A prospective observational pilot study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Another study examining TEG in 270 patients with cirrhosis found that K, α-angle, and MA correlated well with platelet count and fibrinogen in all subgroups, regardless of cirrhosis etiology. 25 A smaller study in 28 patients with mild, chronic liver disease presenting for liver biopsy showed no significant correlation between INR and TEG R. 26 Only two of the patients in the study, however, had an elevated INR (at very modest levels of 1.26 and 1.7).…”
Section: Thromboelastographymentioning
confidence: 86%
“…Another study examining TEG in 270 patients with cirrhosis found that K, α-angle, and MA correlated well with platelet count and fibrinogen in all subgroups, regardless of cirrhosis etiology. 25 A smaller study in 28 patients with mild, chronic liver disease presenting for liver biopsy showed no significant correlation between INR and TEG R. 26 Only two of the patients in the study, however, had an elevated INR (at very modest levels of 1.26 and 1.7).…”
Section: Thromboelastographymentioning
confidence: 86%